ASSOCIATIONS AMONG BETA-LACTOGLOBULIN GENOTYPES AND SOME PRODUCTION TRAITS IN SHEEP: A SYSTEMATIC REVIEW AND META-ANALYSIS - M. Ozdemir1; N. Esenbuga (Journal of Animal and Plant Sciences, 2020)
Researchers have found contradictory evidence for the association between beta-Lactoglobulin (βlg) polymorphism and certain production traits in sheep. The aim of the study is to explore the use of meta-analysis using different genetic models in relations to βlg polymorphism in sheep for the purpose of investigating the association among βlg genes and certain production traits, such as total milk yield, fat, protein, casein and lactose content. As a result of the analysis, the association between βlg genotypes, protein and casein content was determined to be statistically significant (p<0.05). It was found out that the mean value was superior in favor of AA genotype for total milk yield, AB genotype for protein content and casein content especially in dairy subgroup. However, the association among βlg genotypes and other yield properties was determined to be insignificant (p>0.05).
Keywords: Sheep; Meta-analysis; βlg polymorphism; genetic model; production traits